Cross Culture of Religion Sebagai Modal Sosial dalam Mempertahankan Harmonisasi Sosial Umat Beragama di Desa Rama Agung, Bengkulu - Aji, Harun Sukma; Renaldi, Bintang; Oktaviani, Reza; Nopianti, Heni; Himawati, Ika Pasca (Indonesian Journal of Religion and Society, 2024)
This research focuses on how the cross culture of religion becomes social capital in maintaining religious harmonization in Rama Agung Village. In order to identify and examine in depth the social harmonisation created through the cross culture of religion in Rama Agung Village, the research method used is descriptive qualitative. Data collection techniques were non-participant observation, semi-structured interviews, and document studies. The informants are people who know and understand the research topic and come from different religious and ethnic backgrounds. The data analysis technique used the Miles and Huberman approach. The results showed that the cross culture of religion in religious communities in Rama Agung Village includes physical and non-physical aspects. Non-physical aspects include the emergence of values and norms in religious communities in Rama Agung Village related to social harmonisation through daily interfaith actions and behaviours such as visiting each other when adherents of other religions celebrate religious holidays, not disturbing each other in worship and others. The physical aspect is illustrated by the existence of FPUB (Forum of Religious Representatives) and acculturation in building ornaments and public places in Rama Agung Village.